Clinical manifestations of psychogenic non-epileptic seizures in children: Experiences from a single center - Chia-Yih Wang; Ting-Rong Hsu; Kai-Ping Chang (Pediatrics and Neonatology)
Background: This study aimed to determine the clinical features of psychogenic non-epileptic seizures (PNES) and to enhance the accuracy of the differential diagnosis of epilepsy. Methods: This retrospective case series included patients diagnosed with PNES between December 2003 and February 2019 at Taipei Veterans General Hospital. We used International Classification of Diseases (10th revision) codes for screening, and relevant medical records were reviewed. Experienced pediatric neurologists diagnosed PNES based on clinical manifestations, and occasionally on confirmatory video-electroencephalography (EEG) or simultaneous scalp-EEG during the paroxysmal attack. General information, clinical manifestations, psychological conditions, and relevant laboratory or imaging test results were collected and analyzed. Results: Twenty-six patients (mean age, 13 years 8 months) were evaluated, 9 male and 17 female. Ten patients with PNES had a previously established diagnosis of epilepsy. The duration between symptom onset and diagnosis ranged from 1 to 120 (mean, 21; median, 12) days. Sixteen patients showed possible causative psychosocial stressors. Multiple characteristic features or specific clinical manifestations of PNES—that usually differ from epileptic seizures—were observed in all patients with PNES. Conclusion: A detailed evaluation of clinical manifestations and medical history is important for the accurate diagnosis of PNES.